(3eUHGM GdCfGe aj TQM TQGFY GdESdGe cJGH GdTgGOGJs - (3GdfLaj, , GdHOjQj, GdHOjQj, LYaQ Hf CMeO Hf Sja, J (B1369(3g` (B1950(3es ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3bhdg cJGH GdTgGOGJ hGdfXQ aCWQa NeSI, GdChd aj UaGJ GdTghO hjTJQW ajg eFI ChUGa GdChd GdHdhZ adG jbHd TgGOI GdUHj eG des
(3BNQgG (B:s
(3BNQgG(B: (3hCeG GdaQV GdKGfj abO JbOe GdcdGe ajg aj cJGH GdbVGA adGMVg hGddg CYde hGdMeO ddg QH GdYGdejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 121s
(3GdPQjYI, L (B21: 68s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis